Improving online public access catalogs - Yee, Martha M.; Layne, Sara Shatford (American Library Association, 1998)
Technology is improving libraries and the services they offer -- but can your patrons find what they need on your library's OPAC? In this practical guide for librarians and systems designers, the authors describe various OPAC options and explain how users interface with them to obtain information.